Μοριακή οροτύπηση στελεχών της Listeria monocytogenes που απομονώθηκαν στην Κύπρο από ζώα και προϊόντα ζωικής προέλευσης μετά το 2008 - Χριστοφή, Σωτήρης Σ. (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
Listeria monocytogenes is an important foodborne pathogen which causes a serious disease in humans and animals, called listeriosis, and induces major economic loses on food industry, livestock production and national public health systems. For these reasons, it is imperative to exist reliable, fast, affordable and accessible to all food laboratories detection methods, so that a large number of samples can be tested promptly, and efficiently, for the presence of the microbe. In addition, there have to be available methods for epidemiological investigations of listeriosis outbreaks, in order to correlate them with the foods which are the sources of contamination, so that corrective actions can be taken. In the present study, a protocol described first by Doumith et al in 2004 for detection of Listeria monocytogenes and simultaneous identification of its serotype, based on multiplex PCR, was optimized, in order to be applied easily, quickly and economically by any food laboratory in Cyprus. For this, known reference strains of Listeria monocytogenes were used as positive controls and various PCR reaction conditions, ratios of reagents and sample, as well as DNA extraction methods, were compared. After optimization, the method was used for molecular serotyping of Listeria monocytogenes isolates, detected in food of animal origin and from animals, from 2008 until 2012, acquired from the database of Veterinary Services of Cyprus. The identified serotypes could then be correlated with various kinds of food of animal origin, or other sources in order to create the basis for future epidemiological studies. Also, data, on the general situation in Cyprus with regard to Listeria monocytogenes, was collected from all available sources. Based on the results, a laboratory protocol for the detection and identification of Listeria monocytogenes, using multiplex PCR, was developed. It was found that for the incidences of listeriosis on live animals, solely, serotype 4b was responsible, while in food, serotype 1/2a was most frequently found, with 1/2b following. Serotype 1/2c was detected only once in a meat product, whereas 4b was never detected in any food. These results are consistent with the pattern found worldwide, regarding the distribution of serotypes of Listeria monocytogenes, but noteworthy is the fact that the pathogen was never detected in dairy products. This is probably associated with the technology applied for the production of traditional dairy products in Cyprus, which always involves heat treatment.
Keywords: Listeria Monocytogenes; Dairy Products; Γαλακτοκομικά Προϊόντα